Analysis of a solar assisted space heating system with a heat pump and an underground seasonal storage - Inalli, Mustafa; Ünsal, Mazhar (My University, 1997)
A solar assisted space system with a heat pump and a cylindrically shaped seasonal energy storage buried in earth is analysed. The unsteady temperature distribution problem in earth is solved by an application of the finite complex Fourier transform technique and finite differences. The solution obtained is then utilized to calculate the annual performance of the space heating system. The monthly heat load of the house and the monthly collector useful energy were calculated by the degree-day method and the ? + ? method respectively. Effects of the geometric properties of the cylindrical tank and of the thermal properties of earth on the annual performance of the space heating system are estimated numerically.
Yeraltinda mevsimlik depolanan güneş enerjisi ile beslenen isi pompali bir konut isitma sisteminin analizi
Keywords: Heat pump; Seasonal storage; Solar energy; Space heating